Glossário terminológico do açaí: uma perspectiva socioterminológica - OLIVEIRA, Raimunda Rodrigues de (2023)
The present work entitled Açaí Terminology: a socioterminological perspective consists in the elaboration of an Illustrated Terminological Glossary. It is structured semi-systematically (alphabetically) and in conceptual fields (semantic), based on a survey of the terms that characterize the terminology (specialized lexicon) used by a group of professionals, namely: producer, manager of the açai grove, peconheiros, casqueiro, packer, machine operator, beater, bagger, freezer tunnel loader and production manager who have been practicing the craft of planting and processing açaí for more than 10 years at Sitio Santa Maria, located in the rural area and in the agroindustry Aça Vitanat urban area of ​​the City of Igarapé-Miri/Pará. The work is developed from the theoretical assumptions of the sciences of the lexicon with emphasis on Socioterminology and was based on the studies of the following authors: Aragão (2009), Silva (2007), Krieger and Finatto (2004), Barros (2004), Cabré (1995), Faulstich (1995) and Silva and Koch (1995), who discuss the linguistic studies developed by Terminology to the technique of elaborating specialized glossaries. In this perspective, this work has as its main object of analysis and linguistic description of the terminological unit - the term - specialized lexia present in the discourse of professionals who share the same area of ​​human knowledge. The work presents a survey of 200 entries (terms – entry), with a record of terminological variants (lexical, morphosyntactic and socio-professional), whose description and analysis starts from the contexts: social, situational and sociolinguistic in which the terms circulate.